Efficacy of immunotherapy in patients with oncogene-driven non-small-cell lung cancer: a systematic review and meta-analysis - Jiayan Chen; Wanjun Lu; Mo Chen; Zijing Cai; Ping Zhan; Xin Liu; Suhua Zhu; Mingxiang Ye; Tangfeng Lv; Jiawen Lv; Yong Song; Dong Wang (Therapeutic Advances in Medical Oncology, 2024)
Background: Immunotherapy is an emerging antitumor therapy that can improve the survival of patients with advanced non-small-cell lung cancer (NSCLC). However, only about 20% of NSCLC patients can benefit from this treatment. At present, whether patients with driving gene-positive NSCLC can benefit from immunotherapy is one of the hot issues. Therefore, we conducted a meta-analysis to evaluate the efficacy of immunotherapy in patients with oncogene-driven NSCLC and concluded the efficacy of altered subtypes. Methods: A literature search was performed using PubMed, Web of Science, and Cochrane databases. The primary endpoints included the objective response rate (ORR), median progression-free survival (mPFS), and median overall survival (mOS) in patients with oncogene-driven NSCLC. Results: In all, 86 studies involving 4524 patients with oncogene-driven NSCLC were included in this meta-analysis. The pooled ORRs in clinical trials treated with monoimmunotherapy of EGFR, ALK, and KRAS alteration were 6%, 0%, and 23%, respectively. In retrospective studies, the pooled ORRs of EGFR, ALK, KRAS, BRAF, MET, HER2, RET, and ROS1 alteration were 8%, 3%, 28%, 24%, 23%, 14%, 7%, and 8%, respectively. Among them, the pooled ORRs of KRAS non-G12C mutation, KRAS G12C mutation, BRAF V600E mutation, BRAF non-V600E mutation, MET-exon 14 skipping, and MET-amplification were 33% 40%, 20%, 34%, 17%, and 60%, respectively. In addition, the pooled mPFS rates of EGFR, KRAS, MET, HER2, and RET alteration were 2.77, 3.24, 2.48, 2.31, and 2.68 months, while the pooled mOS rates of EGFR and KRAS alteration were 9.98 and 12.29 months, respectively. In prospective data concerning EGFR mutation, the pooled ORR and mPFS treated with chemo-immunotherapy (IC) reached 38% and 6.20 months, while 58% and 8.48 months with chemo-immunotherapy plus anti-angiogenesis therapy (ICA). Moreover, the pooled mPFS and mOS of monoimmunotherapy was 2.33 months and 12.43 months. Conclusions: EGFR-, ALK-, HER2-, RET- , and ROS1 -altered NSCLC patients have poor reactivity to monoimmunotherapy but the efficacy of immune-based combined therapy is significantly improved. KRAS G12C mutation, BRAF non-V600E mutation, and MET amplification have better responses to immunotherapy, and more prospective studies are needed for further research.